Risk Factors of Acute Lower Respiratory Tract Infection:A Study in Hospitallized Central Indian Children under 5 year Age - Deepti, Pandey; ABHA, PANDIT (Innovare Journal of Medical Sciences, 2017)
Background and aim.Preventive measures of regional relevance can be conceived based on understanding of predominant risk factors.Present observational study endeavoured collection of evidence on hierarchy of risk factors for acute lower respiratory infection(ALRI), in under 5 year age children hospitalized in a city in central India. Method.A prospective transactional case control observational study was carried out in 100 hospitallized under 5 year age children of ALRI and 100 healthy babies of similar age and sex composition selected as controls concurrently from immunization and well baby clinic.Hierarchial order of risk factors was elucidated. Result.Low birth weight,incomplete immunization,faulty breast feeding and weaning practices,poor living condition and malnutrition,prematurity and cesarian birth were prominent risk factors for ALRI.First year of life reveals as most vulnerable period in the regard. Conclusion.Risk factors defined by the study are consistent with other reports but,with a variant hierarchial pattern.Good antenatal and immunization care,good breast feeding and nutrition care,restriction of overcrowding and infection ferom family contacts emerged as key prevention perspects.Effective health education and access to basic mother child health services,specially to prematures and those under 1 year age appeared as pertinent preventive interventions against ALRI in preschool babies in specific regional context.